Epoxyeicosatrienoic Acid Analog and 20-HETE Antagonist Combination Prevent Hypertension Development in Spontaneously Hypertensive Rats - Baranowska, Iwona; Gawrys, Olga; Walkowska, Agnieszka; Olszynski, Krzysztof H.; Červenka, Luděk; Falck, John R.; Adebesin, Adeniyi M.; Imig, John D.; Kompanowska-Jezierska, Elżbieta (Frontiers in Pharmacology, 2022)
Numerous studies indicate a significant role for cytochrome P-450 dependent arachidonic acid metabolites in blood pressure regulation, vascular tone and control of renal function. The epoxyeicosatrienoic acids (EETs) exhibit a spectrum of beneficial effects, such as vasodilatory activity, anti-inflammatory, anti-fibrotic, and anti-apoptotic properties. 20-hydroxyeicosatetraenoic acid (20-HETE) is a potent vasoconstrictor that inhibits sodium reabsorption in the kidney. In the present study, the efficiency of EET-A (a stable analogue of 14, 15-EET) alone and combined with AAA, a novel receptor antagonist of 20-HETE was tested in spontaneously hypertensive rats (SHR). Adult SHR (16-week-old) were treated with two doses of EET-A (10 mg/kg/day or 40 mg/kg/day). In the following experiments, we also tested selected substances in the prevention of hypertension development in young SHR (6-weeks-old). Young rats were treated with EET-A or the combination of EET-A and AAA (both at 10 mg/kg/day). Substances were administered for four-weeks in drinking water. Blood pressure was measured by telemetry. Once a week observation in metabolic cages were performed; urine, blood and tissue samples were collected for further analysis. The combined treatment with AAA + EET-A exhibited antihypertensive efficiency in young SHR, which remained normotensive until the end of the observation in comparison to a control group (systolic blood pressure 134±2 versus 156±5 mmHg, respectively; p<0.05). Moreover the combined treatment also increased nitric oxide metabolite excretion. Considering the beneficial impact of the combined treatment with EET-A and AAA in young rats and our previous positive results in adult SHR, we suggest that it is a promising therapeutic strategy not only for the treatment, but also prevention of hypertension.